Chronic conditions and healthcare cost and utilization among underserved Medicare beneficiaries - Karen Fredriksen Goldsen; Hyun-Jun Kim; Natalie R. Turner; Charles A. Emlet (PLoS ONE, 2026)
Underserved older adults face increased risk for certain chronic conditions and multimorbidity, yet research on healthcare spending and utilization in these groups is limited. For example, there is a glaring absence of research on sexual and gender minority (SGM) Medicare beneficiaries. To address this gap, this study uses linked data from Aging with Pride: National Health, Aging and Sexuality/Gender Study (NHAS) and CMS Chronic Conditions Warehouse data (n = 902) to examine chronic conditions, healthcare spending and utilization among a diverse sample of SGM older adult Medicare beneficiaries. Chronic condition complexity was identified using the Medicare Chronic Conditions/Other Chronic Conditions files. Additional explanatory variables included adverse experiences, psychological and social resources, health-related indicators, socioeconomic factors, and background characteristics. The Cost and Use file was used to calculate four outcome variables: total Medicare spending, spending on physician services, high-cost beneficiary status, and healthcare utilization. A series of linear and logistic regressions were used to estimate the association between explanatory and outcome variables. SGM older adult participants with the greatest severity and complexity of chronic conditions had significantly higher total Medicare spending, spending on physician services, and were more likely to be a high-cost beneficiary and higher use of healthcare services compared to those who were comparatively healthy. We also find strong evidence linking higher Medicare spending to disability and dual eligibility, highlighting an urgent need for research given SGM older adults’ increased risk for disabling chronic conditions, yet at times lower healthcare utilization. Higher day-to-day discrimination was associated with greater likelihood of chronic condition complexity and lower Medicare spending. Understanding the relationship between chronic health conditions and healthcare cost and utilization is a critical step in developing responsive health services and effective interventions to promote healthy aging in our increasingly diverse yet often underserved communities.